Enzalutamide-Resistant Progression of Castration-Resistant Prostate Cancer Is Driven via the JAK2/STAT1-Dependent Pathway - Luo, Yong; Yang, Xiaobing; Basourakos, Spyridon P.; Zuo, Xuemei; Wei, Dechao; Zhao, Jiahui; Li, Mingchuan; Li, Qiankun; Feng, Tao; Guo, Pengju; Jiang, Yongguang (Frontiers in Molecular Biosciences, 2021)
Previous studies showed that CXCR7 expression was upregulated after enzalutamide (ENZ) treatment, and an increased level of CXCR7 could increase the invasion, migration, and angiogenesis of castration-resistant prostate cancer (CRPC) cells. This study demonstrated that the levels of p-JAK2, p-STAT1, C-Myc, and VEGFR2 were significantly reduced after CCX771, a specific CXCR7 inhibitor, treatment. This effect further increased after the combination treatment of ENZ and CCX771. Then, we verified that targeting the inhibition of JAK2 or STAT1 could remarkably increase apoptosis and DNA damage and decrease the migration of CRPC cells. More importantly, the combination treatment of ENZ + JAK2/STAT1 led to much greater suppression than the single-agent treatment of JAK2 or STAT1. Subcutaneous CRPC xenograft tumor growth was also reduced by single-agent ENZ treatment and single-agent FLUD, a specific STAT1 antagonist, treatment; but much superior effect was elicited by the combination treatment of ENZ + FLUD. The proliferative indices significantly decreased following combination treatment in tumor tissues compared with control-treatment tissues and single-agent-treatment tissues. Our results demonstrated that CXCR7, which signifies an androgen receptor (AR)-independent signaling pathway, caused CRPC progression via the downstream JAK2/STAT1 signal transduction cascade. Combined inhibition targeting both the AR and JAK2/STAT1 resulted in substantial tumor suppression due to the reduction in DNA damage repair ability and increment in apoptosis.